PENGARUH JOB EMBEDDEDNESS, EMOTIONAL INTELIGENCE DAN EMPLOYEE ENGAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PT. NUSANTARA MOBIL INTERNATIONAL - Ristiarli, Amara Andini; Nugroho, Novianto Eko (Jurnal Ekonomi Dan Bisnis, 2024)
This research aimed to find out, analyze, and test the effect of job embeddedness, emotional intelligence, and employee engagement on organizational citizenship behavior (OCB) for employees of PT Nusantara Mobil International. The job embeddedness was measured by fit, links, and sacrifice. Moreover, emotional intelligence was measured by self-awareness, self-control, self-motivation, social awareness, and social skills. Employee engagement was measured by vigor, dedication, and absorption. The research was quantitative. Furthermore, the population was employees of PT Nusantara Mobil International which consisted of 74 people. The data collection technique used saturated sampling, in which members of the population were the sample.  Additionally, a questionnaire was used as the data collection method. In this research, the data analysis technique is based on multiple linear regression using SPSS software version 25.0. The results concluded that job embeddedness has a positive and significant impact on organizational citizenship behavior. Similarly, both emotional intelligence and employee engagement had a positive and significant impact on organizational citizenship behavior.